Perlindungan Hukum Terhadap Anak yang Berhadapan Berhadapan Dengan Hukum Dalam Kecelakaan Lalu Lintas - Laras Astuti (Justitia Jurnal Hukum, 2017)
Traffic accidents can occur in children. Delinquency due to reckless driving does notrespect fellow road users often make children vulnerable to traffic accidents. This study aims to determine the form of the protection of children in conflict with the law which caused the death of another person along with recovery efforts. This research is normative juridical approach statute approach. The results showed that children in conflict with the legal form of the solution is to use a system of diversion is to perform the transfer of the case out of the criminal justice system. Restorative justice approach is used to emphasize the recovery process into its original state in order to fulfill therights and obligations of both the children in facing law conflict. Recommendations arechildren in conflict with the law should be given protection in order to return in its original state both physically and psychologically so that kids really can again becomea better person and not repeat their delinquency again.Key Words: Children, Traffic accident, Legal protection